2008
DOI: 10.1534/genetics.108.089128
|View full text |Cite
|
Sign up to set email alerts
|

The Small Ubiquitin-Like Modifier (SUMO) and SUMO-Conjugating System ofChlamydomonas reinhardtii

Abstract: The availability of the complete DNA sequence of the Chlamydomonas reinhardtii genome and advanced computational biology tools has allowed elucidation and study of the small ubiquitin-like modifier (SUMO) system in this unicellular photosynthetic alga and model eukaryotic cell system. SUMO is a member of a ubiquitin-like protein superfamily that is covalently attached to target proteins as a post-translational modification to alter the localization, stability, and/or function of the target protein in response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
38
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 75 publications
7
38
0
Order By: Relevance
“…CrUBC3 Is Most Likely the Second SUMO E2 Conjugase Gene in C. reinhardtii Previous analyses of potential SUMO E2 conjugases in C. reinhardtii (Wang et al, 2008) suggested that, among the candidate genes, CrUBC9 was the most similar to verified SUMO E2 conjugase genes found in other eukaryotic organisms. In that same analysis, however, it was noted that the distinction between some of the candidate enzymes as SUMO conjugases versus ubiquitin conjugases was uncertain (Wang et al, 2008).…”
Section: Crubc9 Is Dispensable For Sumoylation Under Nonstress Conditmentioning
confidence: 95%
See 3 more Smart Citations
“…CrUBC3 Is Most Likely the Second SUMO E2 Conjugase Gene in C. reinhardtii Previous analyses of potential SUMO E2 conjugases in C. reinhardtii (Wang et al, 2008) suggested that, among the candidate genes, CrUBC9 was the most similar to verified SUMO E2 conjugase genes found in other eukaryotic organisms. In that same analysis, however, it was noted that the distinction between some of the candidate enzymes as SUMO conjugases versus ubiquitin conjugases was uncertain (Wang et al, 2008).…”
Section: Crubc9 Is Dispensable For Sumoylation Under Nonstress Conditmentioning
confidence: 95%
“…It was previously shown that multiple high-M r proteins are SUMOylated in C. reinhardtii in response to a heat shock of 428C (Wang et al, 2008). To determine if mut5, which lacks the CrUbc9 gene, is capable of this stress-induced SUMOylation, wild-type and mut5 cultures were shifted to 428C for 1 h, and the patterns of SUMOylation in these cultures were detected and analyzed on immunoblots using anti-SUMO antibodies (Fig.…”
Section: Crubc9 Is Dispensable For Sumoylation Under Nonstress Conditmentioning
confidence: 99%
See 2 more Smart Citations
“…The components of SUMO conjugation and deconjugation systems are observed in many plant species, including algae, dicots and monocots. [1][2][3] SUMOylation is involved in many plant physiological processes, such as controlling cell growth and development, embryogenesis and flowering time regulation. 4 It is also involved in actions of both biotic and abiotic stresses, including phosphate starvation responses, salicylic acid-dependent pathogen defense, freezing and cold tolerance, basal thermotolerance and drought response.…”
Section: Introductionmentioning
confidence: 99%